Oil Price and Corporate Social Responsibility Disclosure (CSRD): Evidence from Indonesian Energy Companies - Mandagie, Wenny Candra; Susanto, Kiandra Putri; Endri, Endri; Wiwaha, Arjuna (International Journal of Energy Economics and Policy, 2024)
This study aims to examine the effect of world oil prices and other fundamental factors, which consist of the exchange rate, inflation, return on assets (ROA), debt to equity ratio (DER), and current ratio (CR) to the disclosure of corporate social responsibility (CSRD). The research sample is seven mining sector companies listed on the Indonesia Stock Exchange during 2017-2022. The estimation method and data analysis used a panel data regression model. The study's empirical findings show that world oil prices, exchange rates, inflation, and ROA positively affect CSRD, while DER and CR have the opposite effect. Macroeconomic variables, including world oil prices, exchange rates, and inflation, significantly encourage mining sector companies to disclose CSR more broadly. The increasing liquidity causes limited CSRD and leverages financial performance, while the profitability of the impact is different.